Mini Economica Media Komunikasi Ilmu Ekonomi : Loyalitas Terhadap Tim Olahraga : Mengintegrasikan Pendekatan Pemasaran Relasional dan Hirarki Efek (Studi Kasus pada Persib Bandung dan Persija) - Rivaldho, Abdul Aziz, Achyar, Adrian, dkk (Fakultas Ekonomi dan Bisnis Universitas Indones, 2015)
In sport industry ,loyalty was considered as one of the most important aspect as the lack of match control often to happen. Therefore , relational approach in needed in order to create supporters loyalty. Moreover, hieararchy of effects; cognition-affection-conation is needed to describe further the relationship between consumers and the club itself. This research used Structural Equation Modelling with Lisrel 8.51 as the statistical software.Furthemore, this research found that team self expression has a positif influence towards team attachment influence towards team attachment.